Astrocytic DLL4-NOTCH1 signaling pathway promotes neuroinflammation via the IL-6-STAT3 axis - Mora, Pierre; Laisné, Margaux; Bourguignon, Célia; Rouault, Paul; Jaspard-Vinassa, Béatrice; Maître, Marlène; Gadeau, Alain-Pierre; Renault, Marie-Ange; Horng, Sam; Couffinhal, Thierry; Chapouly, Candice (Journal of neuroinflammation, 2024)
Under neuroinflammatory conditions, astrocytes acquire a reactive phenotype that drives acute inflammatory injury as well as chronic neurodegeneration. We hypothesized that astrocytic Delta-like 4 (DLL4) may interact with its receptor NOTCH1 on neighboring astrocytes to regulate astrocyte reactivity via downstream juxtacrine signaling pathways. Here we investigated the role of astrocytic DLL4 on neurovascular unit homeostasis under neuroinflammatory conditions. We probed for downstream effectors of the DLL4-NOTCH1 axis and targeted these for therapy in two models of CNS inflammatory disease. We first demonstrated that astrocytic DLL4 is upregulated during neuroinflammation, both in mice and humans, driving astrocyte reactivity and subsequent blood-brain barrier permeability and inflammatory infiltration. We then showed that the DLL4-mediated NOTCH1 signaling in astrocytes directly drives IL-6 levels, induces STAT3 phosphorylation promoting upregulation of astrocyte reactivity markers, pro-permeability factor secretion and consequent blood-brain barrier destabilization. Finally we revealed that blocking DLL4 with antibodies improves experimental autoimmune encephalomyelitis symptoms in mice, identifying a potential novel therapeutic strategy for CNS autoimmune demyelinating disease. As a general conclusion, this study demonstrates that DLL4-NOTCH1 signaling is not only a key pathway in vascular development and angiogenesis, but also in the control of astrocyte reactivity during neuroinflammation.